Transnational business education: are we fully building on cultural and linguistic diversity? - Briguglio, Carmela (Marketing and Public Relations Office, Curtin Business School, 2004)
This paper examines issues related to the provision of 'international' business education by Australian universities. In this context, the paper raises questions about the role of universities, the sort of education they currently provide and whether issues related to 'growing wisdom' are in fact being tackled In particular, Australian universities seem to be under-utilising opportunities to teach about cultural diversity and intercultural communication provided by their highly diverse student populations. While claims are easily made about preparing graduates for 'international' or 'global' workplaces, the reality is that knowledge about cultural and linguistic diversity, so necessary in today's business environments, does not seem to be actively pursued. This paper suggests a number of strategies that could be implemented to build upon the opportunities provided by the cultural and linguistic diversity of the student body in Australian tertiary institutions.